Deep learning-based super-resolution climate simulator-emulator framework for urban heat studies - Wu, Yuankai; Teufel, Bernardo; Sushama, Laxmi; Bélair, Stéphane; Sun, Lijun (Geophysical Research Letters, 2021)
This proof-of-concept study couples machine learning and physical modeling paradigms to develop a computationally efficient simulator-emulator framework for generating super-resolution (<250 m) urban climate information, that is required by many sectors. To this end, a regional climate model/simulator is applied over the city of Montreal, for the summers of 2019 and 2020, at 2.5 km (LR) and 250 m (HR) resolutions, which are used to train and validate the proposed super-resolution deep learning (DL) model/emulator. The DL model uses an efficient sub-pixel convolution layer to generate HR information from LR data, with adversarial training applied to improve physical consistency. The DL model reduces temperature errors significantly over urbanized areas present in the LR simulation, while also demonstrating considerable skill in capturing the magnitude and location of heat stress indicators. These results portray the value of the innovative simulator-emulator framework, that can be extended to other seasons/periods, variables and regions.